2021
DOI: 10.3390/urbansci5040072
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Information Gaps on Deprived Urban Areas (Slums) in Low-and-Middle-Income-Countries: A User-Centered Approach

Abstract: Routine and accurate data on deprivation are needed for urban planning and decision support at various scales (i.e., from community to international). However, analyzing information requirements of diverse users on urban deprivation, we found that data are often not available or inaccessible. To bridge this data gap, Earth Observation (EO) data can support access to frequently updated spatial information. However, a user-centered approach is urgently required for the production of EO-based mapping products. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The feature selection algorithms, predictions, and accuracy measurements were performed through the R statistical software. The GEOBIA-related code and resultant maps are publicly available in the Zenodo scientific repository [35].…”
Section: Geographic Object-based Image Analysis Processing (Geobia)mentioning
confidence: 99%
“…The feature selection algorithms, predictions, and accuracy measurements were performed through the R statistical software. The GEOBIA-related code and resultant maps are publicly available in the Zenodo scientific repository [35].…”
Section: Geographic Object-based Image Analysis Processing (Geobia)mentioning
confidence: 99%
“…However, most EObased mapping studies on DUAs work at a city scale or below (Ajami et al 2019;Badmos et al 2018;Wurm et al 2019) and do not deal with the main challenges of scalable, transferable, and low-cost solutions (Kuffer 2020). To date, EO data have not shown their capabilities to provide adequate monitoring instruments supporting knowledge on the location, characterisation, and dynamics of DUAs (Kuffer et al 2021b), e.g., supporting local SDG 11.1.1 reviews. A recently published needs assessment of different user groups that require such data (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A recently published needs assessment of different user groups that require such data (Fig. 1.2) has shown that data are needed for a fine-grained spatial scale (e.g., gridded data at 100 m) with an update cycle of 1-2 years (Kuffer et al 2021b). Generally, urban development questions require city-scale information and detailed neighbourhood analysis (Kuffer et al 2018;Merodio Gómez et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Linked to this is the necessity of more systematic data (UN-Habitat, 2015b). Although there is innumerable literature about poverty, systematic documentation of physical living forms of poverty rarely exists (Kuffer, Wang, et al, 2021). Many studies are descriptive in nature, e.g., UN-Habitat (2003); Davis (2011); Hofmann et al (2008); Kohli et al (2012).…”
Section: Introductionmentioning
confidence: 99%